Teaching English Communication Skills with NLP (Neurolinguistic Programming) - Riyono, Ahdi (ENCOUNTER, 2012)
This paper describes the use of NLP in the teaching of English communication. Actually, there are two kinds of communication, verbal and non verbal communication. So that in teching English for communication, those kinds of communication should be extreamly considered. Many methods of teaching employed which are still based on humanistic methods consisting of community language learning (CLL), suggestopedia, the Silent Way, Total Physical Response (TPR) and natural approach focuse only on verbal communication. In fact, in communication, both verbal and nonverbal aspects are important to comprehend. So far, there are still many students who are frustrated at being unable to express themselves, and to communicate among people although they have been learning English for many years. In NLP, the language learning process is how learners experience the world, and how to decrease the anxiety of learners who are learning English. The increasing propularity of NLP in English language teaching is a reflection on the low self-esteem of educators and students.